PRODUKTIVITAS PRIMER Kappaphycus alvarezii BERDASARKAN PERBEDAAN BIOMASSA AWAL DI PERAIRAN BONE-BONE - Agista Ariani (JKP - Jurnal Kelautan dan Pesisir, 2025)
Primary productivity is an important factor in marine ecosystems, as it plays a vital role in the carbon cycle and food chain for heterotrophic organisms. The purpose of this study was to determine the level of primary productivity and analyze how the initial biomass of K. alvarezii produced in Bone-Bone Waters differs. The benefit of this study is that it can provide information and help strengthen understanding of the role of K. alvarezii in supporting primary productivity and the balance of the Bone-Bone aquatic ecosystem. This study was conducted from November 2024 to March 2025 at Bone-Bone Beach, Bau-Bau City, Southeast Sulawesi. The results showed that the initial biomass treatment of 30 g produced the highest gross and net primary productivity values ​​compared to the 10 g and 20 g treatments. The respiration value in the treatment with a higher biomass was due to increased tissue metabolic activity. Higher biomass means there are more physiologically active cells, so the respiration process also increases.